The Effect of Environmental Education Learning on Students at University - Suarlin Suarlin; Muhammad Ichsan Ali (International Journal of Environment, Engineering and Education, 2020)
The commitment to environmental improvement through education has been included in the agenda this century. One formulation state that education plays an essential role in achieving a shared vision of realizing sustainable development. The specific steps are taken from Agenda 21 formulated in Education for Sustainable Development. The specific objectives to achieve from this research are as follows 1) Identifying the effect of environmental education on environmentally friendly attitudes of students; 2) Identifying the effect of environmental education on environmentally friendly behavior of students. The number of samples used in the study was 216 respondents. The data analysis technique used in this study is the Confirmatory Factor Analysis (CFA). From the results obtained for the energy conservation variable, the behavior towards conservation shows that there is still a lack of students conserving energy in their daily lives. An attitude of caring for the environment is a willingness that arises from internal encouragement to declare caring action for the environment, improve or maintain the environment's quality. Environmental care is intended as a change in the behavior of learning outcomes shown through understanding, experience, and mental readiness of students in applying the knowledge they learn through social processes to respond consistently to particular objects in a direction that supports or rejects and agrees or disagrees with an object.